Risk for intracranial hemorrhage in individuals after mild traumatic brain injury who are taking serotonergic antidepressants - Isokuortti, Harri; Iverson, Grant L.; Posti, Jussi P.; Berghem, Ksenia; Kotilainen, Anna-Kerttu; Luoto, Teemu M. (Frontiers in Neurology, 2022)
Background Serotonergic antidepressants may predispose to bleeding, but little is known of the risk for traumatic intracranial bleeding. Methods This was a prospective case-control study of 218 patients with mild traumatic brain injuries (TBI) who were treated at a Finnish tertiary trauma hospital. Injury-related information and clinical findings were prospectively collected in the emergency department. Detailed pre-injury health history was collected from electronic medical records. Information on the use of serotonergic antidepressants was attained from the Finnish national prescription registry. All head CT scans were reviewed by a neuroradiologist based on the Common Data Elements. Cases were patients with traumatic intracranial hemorrhage on head CT. Controls were patients from the same cohort, but without traumatic intracranial lesions on CT. The proportion with traumatic intracranial bleeding for patients on serotonergic antidepressant medication was compared to the proportion for patients not on serotonergic medication. Results The study cohort consisted of 24 cases with traumatic intracranial bleeding and 194 injured controls. The median age of the sample was 70 years (interquartile range = 50–83). One fifth (21.6%) of all the patients were taking a serotonergic antidepressant. Of the patients on an antidepressant, 10.6% (5/47) had an acute hemorrhagic lesion compared to 11.1% (19/171) of those who were not on an antidepressant (p = 0.927). In the regression analysis, traumatic intracranial hemorrhage was not associated with antidepressant use. Conclusion Serotonergic antidepressant use was not associated with an increased risk of traumatic intracranial hemorrhage after a mild TBI. The patients in this relatively small cohort were mostly middle-aged and older adults. These factors limit the generalizability of the results in younger patients with mild TBI.